The adding value of fluid challenge and balloon occlusion tests in patients with atrial septal defect. (14th October 2021) - D'Alto, M; Chessa, M; Santoro, G; Giordano, M; Gaio, G; Romeo, E; Argiento, P; Wacker, J; D'Aiello, F; Sarubbi, B; Russo, M G; Golino, P; et al.
Abstract: Background: Careful, step-wise assessment is required in all patients with an atrial septal defect (ASD) to exclude pre-existing pulmonary vascular disease or left ventricular disease. Fluid challenge test (FCT) and balloon occlusion testing (BOT) may unmask left ventricular disease and challenge the pulmonary circulation, but their complementary role in the evaluation of patients with "operable" ASD is not well established. Aim: To evaluate the haemodynamic changes of the pulmonary circulation by FCT and BOT in ASD patients undergoing percutaneous closure according to the current guidelines. Methods: Consecutive patients selected for percutaneous ASD closure underwent invasive hemodynamic assessment at baseline and after BOT, FCT and both. Results: Fifty patients (mean age 47.3±11.7 years, 72% female) were included. All patients had a pulmonary-to-systemic flow ratio (QP/QS) ≥1.5, pulmonary vascular resistance (PVR) <5 WU and pulmonary arterial wedge pressure (PAWP) <15 mmHg. Individuals with a PVR ≥2 WU at baseline were older, more symptomatic, with a higher baseline systemic vascular resistance compared to the lower PVR group (PVR <2 WU; p<0.0001). The response of Qp/Qs to FCT was different between groups (p<0.0001, Figure 1). Patients with a lower baseline PVR experienced an increase in Qp/Qs, which remained above 1.5 in all patients, whereas in almost all (90%) patients with a higher baseline PVR, the Qp/Qs fell to below 1.5. FCT caused a marked increase in pulmonary blood flow of almost 2 liters (p<0.0001) accompanied by increases in PAWP (p<0.0001). BOT led to a modest increase in PAWP (Δ1.5 [−1.0–7.0] mmHg, p<0.0001). FCT added to BOT caused a further increase in PAWP and Qs (both p<0.0001), while PVR was unchanged (p>0.1). No difference was observed in the PAWP response to FCT, BOT or both between groups; no patients reached a PAWP ≥18 mmHg following FCT or BOT alone, but 4 (8%) patients did following the addition of FCT to BOT. No acute clinical adverse events were experienced by any patients. Conclusions: None of the reported ASD patients presented with FCT criteria of post-capillary PH (that is a PAWP >18 mmHg). Even small rises in PVR may have significant implications on cardiovascular haemodynamics. In fact, patients with PVR <2 WU showed an increase in Qp/Qs, which remained above 1.5 in all patients, suggesting that they still had a distensible pulmonary circulation, whereas in almost all patients with a PVR ≥2 WU, the Qp/Qs fell to below 1.5. FUNDunding Acknowledgement: Type of funding sources: None.